2020
DOI: 10.3390/v12050526
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2/COVID-19: Viral Genomics, Epidemiology, Vaccines, and Therapeutic Interventions

Abstract: The COVID-19 pandemic is due to infection caused by the novel SARS-CoV-2 virus that impacts the lower respiratory tract. The spectrum of symptoms ranges from asymptomatic infections to mild respiratory symptoms to the lethal form of COVID-19 which is associated with severe pneumonia, acute respiratory distress, and fatality. To address this global crisis, up-to-date information on viral genomics and transcriptomics is crucial for understanding the origins and global dispersion of the virus, providing insights … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
143
0
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 223 publications
(159 citation statements)
references
References 113 publications
(157 reference statements)
0
143
0
16
Order By: Relevance
“…Some reviews related to patients who received transfusion with CP showed a reduction in viral load, improvement in clinical symptoms, better radiological findings, and improved survival (260,261,(271)(272)(273). In addition, after having received CP containing nAbs, COVID-19 patients had significant improvements from the beginning of treatment (until 22 days), presenting lower fever, decreased viral load, and higher nAbs levels.…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…Some reviews related to patients who received transfusion with CP showed a reduction in viral load, improvement in clinical symptoms, better radiological findings, and improved survival (260,261,(271)(272)(273). In addition, after having received CP containing nAbs, COVID-19 patients had significant improvements from the beginning of treatment (until 22 days), presenting lower fever, decreased viral load, and higher nAbs levels.…”
Section: Antibody-based Therapymentioning
confidence: 99%
“…The impact of the ongoing COVID-19 pandemic on healthcare, social and economic structures across the world is unprecedented. 1 With over 21 million laboratory-confirmed cases globally (as of 17th August 2020), widespread testing to rapidly identify SARS-CoV-2-infected individuals and ensure appropriate implementation of isolation measures and contact tracing has been a crucial element in the strategy to contain the pandemic. Nasopharyngeal swab (NPS) has been used as the gold standard respiratory specimen for SARS-CoV-2 reverse-transcriptase PCR (RT-PCR) tests.…”
Section: Introductionmentioning
confidence: 99%
“…Em 11 de fevereiro de 2020, a Organização Mundial de Saúde (OMS, 2020) nomeou como a doença coronavírus 2019 (COVID-19) [1,2,3] . Em 11 de março, a OMS decretou pandemia devido ao aumentou da propagação do vírus no mundo e o elevado risco de impacto do COVID-19 em nível global [4] .…”
unclassified
“…As evidências atuais sugerem que a SARS-CoV-2 provavelmente é um vírus zoonótico e é transmitido principalmente pela inalação de gotículas infectadas expelidas quando um paciente infectado tosse ou espirra. A contaminação ocorre quando tocamos a mãos em superfícies contaminadas por gotículas e levamos ao rosto, olhos ou nariz [1,6] .…”
unclassified
See 1 more Smart Citation